Pengembangan Usaha Jasa Pasokan dan Pemeliharaan Ban Alat Berat di PT Bukit Jaya Utama - Bukit1, Matius Tomaja; Syarief, Rizal; Kadarisman, Darwin (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2021)
The increasingly intense competition in the business world at this time has made business actors must have "weapons" to serve as an advantage in winning the competition. The ability of business people to meet consumer expectations is needed to win the competition, so a marketing strategy is needed that is able to attract interest and inspire people to buy the goods or services produced by the company. PT Bukit Jaya Utama is a company engaged in the supply and service of heavy equipment. Heavy equipment or large equipment are capital goods with a relatively high investment value, widely used as production tools, usually in public works and mining operations. The objectives of the study are (1) to identify the position of PT Bukit Jaya Utama based on internal and external factors, (2) to find out the study of the development strategy in PT Bukit Jaya Utama's supply and spare parts service business, (3) to develop a development strategy for PT Bukit Jaya Utama. The location of this study was carried out at PT Bukit Jaya Utama, which is located at Vila Mutiara Lido Block D2 No. 32 (ROXY) Cigombong, Bogor 16740 West Java. The results of the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) Matrix and Internal External (IE) Matrix analysis obtained values of 2.651 and 2.482 respectively. Based on the combination of EFE and IFE values, an IE matrix is obtained, with the middle cell position (Growth/Stable). The SWOT analysis (Strengths, Weakness, Opportunities and Threats) shows the following strategies: (a) increasing productivity, (b) improving service, (c) increasing the efficiency of procurement of raw materials, (d) increasing sales volume with marketing effectiveness, (e) maintaining and maintaining product quality, (f) increasing cooperation with suppliers, (g) improving production technology and product quality, and (h) improving distribution channels. Quantitative Strategic Planning Matrix (QSPM) analysis calculations produce three main strategies for PT Bukit Jaya Utama, namely (a) improving services, (b) improving production technology and product quality and (c) maintaining and maintaining the quality of the products produced.